X.25 AS ONE OF DATA COMMUNICATIONS PROTOCOL STANDARDS - Milya Rosanty; I. Rafael Abdul Gafar I. Rafael Abdul Gafar (Jurnal Sistem Informasi, 1994)
Data communications technology today has become a necessity that can becategorized fairly important role to meet the demand for exchange of data /information quickly and accurately in line with the growing computer andtelecommunications technologies in the information age which is increasinglygrowing rapidly as now .Engineered to be able to form a data communication network was started severalyears ago and continue growing until the present, with one of their productengineering and it is a protocol that became one of the components of datacommunication, that is all things relating to procedures for setting up and utilizationof resources power of the respective data communications network.One of the protocols are quite dominant in the field of data communications today isthe X.25 protocol-oriented technology with an emphasis on efficiency and cost, andthe broader needs of the prototype of the X.25 protocol has been standardized byCCITT in 1976 became the standard protocol .The mechanism of this X.25 protocol uses the concept of seven layers as a reference,where the practice takes advantage of Layer 1 protocols (Physical Layer), Layer 2(Data Link Layer) and Layer 3 (Network Layer) of the concept of the OSI 7 layer. Byapplying these concepts in a standard protocol in-merela recognized by those who areinvolved in the field of data communications worldwide.